Problem solving and programming concepts - Sprankle, Maureen (Pearson/Prentice Hall, 2009)
Revised to reflect the most current issues in the programming industry, this successful book emphasizes that problem solving is the same in all computer languages, regardless of syntax. Uses a generic, non-language-specific approach to present the tools and concepts required when using any programming language to develop computer applications. Is designed for readers with little or no computer experience, but is also useful to programmers at any level. Provides step-by-step progression and consistent in-depth coverage of topics, with detailed explanations and many illustrations. Covers topics ranging from the basics of mathematical functions and operators to the design and use of such techniques as code, arrays, pointers, other data structures, database concepts, and object-oriented programming concepts. A useful reference for programmers.